INTERTEXTUALITY INTERTEXTUALITY OF PATANJALI'S YOGA SUTRA PHILOSOPHY: - - I Gusti Made Widya Sena; I Made Adi Brahman (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2026)
This research starts from the view that the existence of a philosophical thought cannot stand alone. Yoga is a school of philosophy (darsana) that cannot be separated from the influence of other knowledge or systems of thought. Furthermore, this research seeks to explore the influence of yoga texts on the existence of the Yoga Sutra text by Rsi Patanjali. This research is classified as qualitative research with data collection methods: library study, document study and online data search. Data were analyzed using hermeneutic techniques with an intertextual approach. The results of the research show that the Vedic civilization has had an influence on the emergence of yoga philosophical thought. Likewise, the influence of the Upanisad texts and the Bhagavad Gita also had an influence on the existence of the Yoga Sutra book by Rsi Patanjali. Rsi Kapila's Samkya darsana also had an important influence on the emergence of Patanjali's philosophical views of yoga sutra.